Certain aspects of visual perception in some "autistic" children - Lazarus, Janet Ray (Department of Psychology, 2016)
Identification strategies and patterns of visual inspection in relation to non-perceptual variables, rapport and discrimination set, were studied in 3 "autistic" Ss, using experimental materials relevant to various forms of visual perception. A qualitative, single case approach was followed, using as controls, individually matched Ss representing various points on a developmental continuum. Marked differences were found between 2 "autistic" Ss as compared with the third "autistic" S and the majority of control Ss in all variables, although 2 young normal Ss exhibited features similar to the 2 "autistic" Ss. It therefore appeared that in some "autistic" Ss, there was disturbance at selective and identifying levels of perception associated with deficiencies in non-perceptual factors. The disturbance appeared developmental rather than deviant in nature.